Industrial training report: Felda D'saji / Alyssa Nor Nor Azhar - Nor Azhar, Alyssa Nor (Universiti Teknologi MARA, Negeri Sembilan, 2024)
This report is about my two-month industrial training experience at Felda D'saji, as well as my personal development during that time. This industrial training program's goal was to expose me to real-world problems and provide me practical industry experience. I got the chance to assist with the company's operations and learn from knowledgeable industry professionals during my training, obtaining insightful knowledge and useful skills in the process.